2014
DOI: 10.1186/1471-2164-15-218
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering gamma-decalactone biosynthesis in strawberry fruit using a combination of genetic mapping, RNA-Seq and eQTL analyses

Abstract: BackgroundUnderstanding the basis for volatile organic compound (VOC) biosynthesis and regulation is of great importance for the genetic improvement of fruit flavor. Lactones constitute an essential group of fatty acid-derived VOCs conferring peach-like aroma to a number of fruits including peach, plum, pineapple and strawberry. Early studies on lactone biosynthesis suggest that several enzymatic pathways could be responsible for the diversity of lactones, but detailed information on them remained elusive. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 49 publications
5
112
0
Order By: Relevance
“…The mapping studies performed in the cultivated strawberry have highlighted regions of extensive homozygosity in the genomes of modern F. ×ananassa cultivars attributed to repeated cycles of breeding and selection of specific loci, as well as rearrangements between the diploid and octoploid genomes [8,10]. Despite the molecular resources that have been developed for the cultivated strawberry, to date, only a few studies have reported the characterization of traits of economic importance [12][13][14][15][16], one of the main difficulties being finding sufficient numbers of markers to efficiently saturate QTL-containing regions of the genome.…”
Section: Introductionmentioning
confidence: 99%
“…The mapping studies performed in the cultivated strawberry have highlighted regions of extensive homozygosity in the genomes of modern F. ×ananassa cultivars attributed to repeated cycles of breeding and selection of specific loci, as well as rearrangements between the diploid and octoploid genomes [8,10]. Despite the molecular resources that have been developed for the cultivated strawberry, to date, only a few studies have reported the characterization of traits of economic importance [12][13][14][15][16], one of the main difficulties being finding sufficient numbers of markers to efficiently saturate QTL-containing regions of the genome.…”
Section: Introductionmentioning
confidence: 99%
“…The Classical Sachima and Premiom Sachima were found to contain the higher relative content of n‐propylacetate with 17.67 and 16.72 μg/kg. Lactones are known to be associated with fruit aromas formed by the intramolecular esterification of hydroxyl acids (Sánchez‐Sevilla, José Cruz‐Rus, Valpuesta, Botella, & Amaya, ; Zhao et al, ). However, in the present study, there were no aroma‐active compounds of the lactones detected by the sensory panelists, it was suggested that lactones are not a key contributor to the aroma profile of Sachima.…”
Section: Resultsmentioning
confidence: 99%
“…Among the many breeding-relevant loci discovered in the cultivated strawberry genome, flowering, and fruit quality loci have been prominent, as would be expected in a high-value fruit commodity. These, include discovery of the locus controlling day-neutrality or PF 51 and its subgenome localization 52 as well as multiple loci controlling volatile compounds such as gamma decalactone, mesifurane, and methyl anthranilate [53][54][55][56] . For uncovering disease resistance loci, quantitative trait locus (QTL) mapping has been the most prominent approach.…”
Section: Genome-assisted Breeding In Strawberrymentioning
confidence: 99%
“…While locus-specific DNA tests are highly useful in parent and seedling selection for traits with simple genetics, genome-wide prediction has become the strategy of choice for improving genetically complex traits in crop species. The goal is predictive, and the utility of this strategy has been demonstrated in strawberry for parent selection for yield and quality traits where it was shown 52 Perrotte et al 84 ; Salinas et al 85 Fruit quality γ-decalactone FaFAD1 qFaFAD1 SCAR Sánchez-Sevilla et al 55 ;…”
Section: Genome-assisted Breeding In Strawberrymentioning
confidence: 99%
See 1 more Smart Citation